Antibiotic or silver versus standard ventriculoperitoneal shunts (BASICS): a multicentre, single-blinded, randomised trial and economic evaluation. Issue 10208 (26th October 2019) - Mallucci, Conor L; Jenkinson, Michael D; Conroy, Elizabeth J; Hartley, John C; Brown, Michaela; Dalton, Joanne; Kearns, Tom; Moitt, Tracy; Griffiths, Michael J; Culeddu, Giovanna; Solomon, Tom; Hughes, Dyfrig; et al.
Summary: Background: Insertion of a ventriculoperitoneal shunt for hydrocephalus is one of the commonest neurosurgical procedures worldwide. Infection of the implanted shunt affects up to 15% of these patients, resulting in prolonged hospital treatment, multiple surgeries, and reduced cognition and quality of life. Our aim was to determine the clinical and cost-effectiveness of antibiotic (rifampicin and clindamycin) or silver shunts compared with standard shunts at reducing infection. Methods: In this parallel, multicentre, single-blind, randomised controlled trial, we included patients with hydrocephalus of any aetiology undergoing insertion of their first ventriculoperitoneal shunt irrespective of age at 21 regional adult and paediatric neurosurgery centres in the UK and Ireland. Patients were randomly assigned (1:1:1 in random permuted blocks of three or six) to receive standard shunts (standard shunt group), antibiotic-impregnated (0·15% clindamycin and 0·054% rifampicin; antibiotic shunt group), or silver-impregnated shunts (silver shunt group) through a randomisation sequence generated by an independent statistician. All patients and investigators who recorded and analysed the data were masked for group assignment, which was only disclosed to the neurosurgical staff at the time of operation. Participants receiving a shunt without evidence of infection at the time of insertion were followed up for at least 6 months and a maximum of 2 years. The primary outcome was time to shunt failure due the infection and was analysed with Fine and Gray survival regression models for competing risk by intention to treat. This trial is registered with ISRCTN 49474281. Findings: Between June 26, 2013, and Oct 9, 2017, we assessed 3505 patients, of whom 1605 aged up to 91 years were randomly assigned to receive either a standard shunt (n=536), an antibiotic-impregnated shunt (n=538), or a silver shunt (n=531). 1594 had a shunt inserted without evidence of infection at the time of insertion (533 in the standard shunt group, 535 in the antibiotic shunt group, and 526 in the silver shunt group) and were followed up for a median of 22 months (IQR 10–24; 53 withdrew from follow-up). 32 (6%) of 533 evaluable patients in the standard shunt group had a shunt revision for infection, compared with 12 (2%) of 535 evaluable patients in the antibiotic shunt group (cause-specific hazard ratio [csHR] 0·38, 97·5% CI 0·18–0·80, p=0·0038) and 31 (6%) of 526 patients in the silver shunt group (0·99, 0·56–1·74, p=0·96). 135 (25%) patients in the standard shunt group, 136 (25%) in the antibiotic shunt group, and 140 (27%) in the silver shunt group had adverse events, which were not life-threatening and were mostly related to valve or catheter function. Interpretation: The BASICS trial provides evidence to support the adoption of antibiotic shunts in UK patients who are having their first ventriculoperitoneal shunt insertion. This practice will benefit patients of all ages by reducing the risk and harm of shunt infection. Funding: UK National Institute for Health Research Health Technology Assessment programme.